Estimation of the effects of physical violence on women in health family in Peru: 2012 - 2016 - Chávez Padilla, Carlos César (2018)
The study focused on how the woman and the woman, her partner, affect her and her child's health. For this, a double economic regression was carried out, where in the first scenario of the double regression a regression of domestic violence was made with respect to the Emergency Center for Women and the control variables; In the second scenario, the regression is performed with the variables that measure the intangible costs for the woman and the child with respect to the domestic violence predicted and calculated in the first regression and the control variables. Having as main results, that women and women can cause the child to suffer from anemia, have gastrointestinal problems, and that the weight of the child at birth is real, the presence of EMF has a relationship with better nutrition of the children. children and etc.